Effect of temperature on kinking failure mode of non-slender glass fiber-reinforced polymer specimens. (1st December 2015) - Sun, Wei; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: The kink behavior of non-slender glass fiber-reinforced epoxy prismatic specimens of variable length and fiber volume fraction at temperatures ranging from 25 °C to 125 °C was investigated. Splitting failure occurred at the glassy state while kinking failure was observed at the glass transition state and buckling with subsequent post-peak kinking at the rubbery state. Kink initiation was caused by the initial imperfections, i.e. the waviness of the unidirectional fibers. Initiation occurred through fiber microbuckling caused by combined compressive and shear stresses at the glass transition state and predominant shear stresses at the rubbery state due to the preceding buckling. The kink band width was narrow at the glass transition state due to the significant compressive stresses and corresponded to the wavelength of the initial fiber waviness. The kink band width at the rubbery state was much wider and corresponded to the band width of the maximum shear stresses at the inflexion points of the buckling shape. The kink band angle depended on the ratio of compressive to shear stresses. The different specimen slendernesses and fiber volume fractions did not influence the kink initiation and kink band formation mechanisms.